PRESCRIBING ERRORS AND INTERVENTION OUTCOMES IN SELECTED TERTIARY HOSPITALS IN NIGERIA (2014)
Prescribing errors, particularly in the medical and paediatric specialties have been reported globally to affect up to 52.0% of hospitalized patients with potential to cause harm. Prescribing errors have however not been adequately investigated in Nigeria. This study was designed to carry out an in-depth evaluation of the nature, severity and causes of prescribing errors in three purposively selected tertiary hospitals in Nigeria with a view to providing pharmacist-led evidence-based recommendations for their prevention. A retrospective review of 8270 out-patient prescriptions and 1200 in-patient records from medical and paediatric units between January and December 2010 in National Hospital, Abuja (NHA) with University of Abuja Teaching Hospital, Gwagwalada (UATH) and University College Hospital, Ibadan (UCH) as controls. Baseline prescribing pattern was measured using the British National Formulary and Nigeria Standard Prescribing Guidelines. Causes of prescribing errors were investigated using a prospective qualitative approach involving semi-structured face-to-face interviews and questionnaires guided by the Reason’s accident causation model. Error rates were studied in the three tertiary hospitals while intervention was carried out at NHA. Interventions involved educational outreaches consisting of structured teaching and training. Data collected compared error rates pre- and post- intervention, to determine impact of the intervention. Data were analysed using descriptive and Chi-square statistics. Prescribing error rates were 24.6 ± 1.4 (UATH), 5.7 ± 1.2 (NHA) and 6.7 ± 2.3 (UCH) for out-patient prescriptions and 28.7 ± 2.3 (UATH), 26.3 ± 2.1 (NHA) and 41.0 ± 3.1 (UCH) for in-patient prescriptions. Non-inclusion of direction of use (38.1%, UATH); missing signature and/or name of prescriber (66.6%, NHA) and omitting end date of therapy (54.4%, UCH) were the commonest errors in out-patient prescriptions. The most common in-patient prescribing error was missing end date of therapy: 71.3% (UATH), 65.9% (NHA) and 86.0% (UCH). The highest proportion of medications was ordered at admission: 57.3% (UATH), 44.3% (NHA) and 44.7% (UCH) while time of discharge was associated with the highest error rates of 37.8% (UATH), 58.6% (NHA) and 80.8% (UCH). Severity of prescribing error rates for in-patients was 4.9% (UATH), 2.8% (NHA) and 1.3% (UCH). Prescriptions involving antimicrobials contained the highest prescribing UNIVERSITY OF IBADAN LIBRARY iii errors 53.8% (UATH), 37.9% (NHA), and 36.3% (UCH). Risk factors identified in error causation included organisational (91.0%), environment (50.0%), individual (45.0%), task (45.0%) and team (36.0%) factors. Absence of self-awareness of errors and organisational factors identified included inadequate training and experience and absence of reference materials. Defences against errors, particularly pharmacists’ involvement, were deficient. There was no change in overall error rates 5.8%, pre- and post- intervention (p = 0.98). However, there were reductions in drug-drug interactions 1.2% to 0.4% (p<0.001), omission of drug route 0.3% to 0.1% (p<0.001) and ambiguous orders 0.2% to 0.0% (p<0.001) at the NHA. Prescribing errors were common in the 3 facilities resulting from writing prescriptions that lacked details and slips in attention. Majority of the errors, though of minor severity, had potential of causing harm. Continuing prescriber education and training will likely result in error reduction. Pharmacists’ involvement in prescribing error prevention should be an on-going process. Key words: Prescribing errors, Reason’s accident causation model, In- and out-patients. Word count: 500